THE ANALYSIS OF THE STUDENTS’ PERCEPTIONS IN LEARNING ENGLISH STANDARDIZED TESTS TOWARDS THEIR LEARNING MOTIVATION - Yanuar Dwi Prastyo; Roro Wulandari (BEYOND LINGUISTIKA (Journal of Linguistics and Language Education), 2021)
In present time, Learning English is crucial since it has become the language used by many people in the world. Beside should be learnt the people should also be able to measure their proficiency. Therefore, the Standardized tests are needed. The objective of this research is to explore the students’ perceptions in learning English Standardized tests (TOEFL, IELTS, & TOEIC) towards their learning motivation in 7th semester students of English Department Universitas Bandar Lampung. The approach used is qualitative approach. Descriptive and thematic analysis was used to conduct this research. I used questionnaire and interview to the 7th semester students in gathering the data about their perception in learning English Standardized tests towards their learning motivation. The results and discussion show that the findings of the present study revealed that overall, of the students’ perceptions in learning English Standardized tests are quite positive. Based on three themes used to categories the student’s perceptions, learning English Standardized tests involved positive impact to the student’s perception through promoting the students’ learning motivation whether it is intrinsic motivation or extrinsic motivation, challenging the students in the learning process and developing the students’ skills in the test’s performances and the English competencies.